2006
DOI: 10.1371/journal.pbio.0040215
|View full text |Cite
|
Sign up to set email alerts
|

Functional Imaging Reveals Numerous Fields in the Monkey Auditory Cortex

Abstract: Anatomical studies propose that the primate auditory cortex contains more fields than have actually been functionally confirmed or described. Spatially resolved functional magnetic resonance imaging (fMRI) with carefully designed acoustical stimulation could be ideally suited to extend our understanding of the processing within these fields. However, after numerous experiments in humans, many auditory fields remain poorly characterized. Imaging the macaque monkey is of particular interest as these species have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

33
253
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(288 citation statements)
references
References 49 publications
33
253
2
Order By: Relevance
“…Here, we report conclusive fMRI evidence for the existence of orthogonal tonotopic and periodotopic gradients forming complete AFMs in human core and belt auditory cortex. The presence of orthogonal gradients allowed the identification of 11 maps consistent with the human cytoarchitectural measurements (19)(20)(21)(22) and with proposed homology to the 11 core and belt auditory subfields in macaque auditory cortex (10,11,17,18). More broadly, we found that the 11 AFMs are organized into the radially orthogonal "clover leaf" clusters, similar to what has been reported as an organizing principle of VFMs in human visual cortex (4,6,7,9,(35)(36)(37).…”
supporting
confidence: 85%
See 2 more Smart Citations
“…Here, we report conclusive fMRI evidence for the existence of orthogonal tonotopic and periodotopic gradients forming complete AFMs in human core and belt auditory cortex. The presence of orthogonal gradients allowed the identification of 11 maps consistent with the human cytoarchitectural measurements (19)(20)(21)(22) and with proposed homology to the 11 core and belt auditory subfields in macaque auditory cortex (10,11,17,18). More broadly, we found that the 11 AFMs are organized into the radially orthogonal "clover leaf" clusters, similar to what has been reported as an organizing principle of VFMs in human visual cortex (4,6,7,9,(35)(36)(37).…”
supporting
confidence: 85%
“…In audition, there has been only one dimension of sensory topography clearly mapped in cortex, which makes it impossible to use sensory topography to accurately differentiate specific human cortical auditory field maps (AFMs). Current estimates of human AFMs rely primarily on a monkey model that is well characterized by cytoarchitectonics (10,11), single-and multiunit physiology (12)(13)(14)(15)(16), tracer studies (17), and functional magnetic resonance imaging (fMRI) (18). Human cytoarchitectonic measurements generally resemble those in macaque monkey and indicate that the small subfields of primary auditory cortex are confined to Heschl's gyrus (HG; or between HG-1 and HG-2, in cases where a double gyrus exists) and oriented medial to lateral along HG (19)(20)(21)(22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…S4A). To further localize the caudal auditory region with respect to functionally defined auditory fields, we exploited a described mapping procedure, which provides a functional parcellation of auditory cortex based on the tonotopic organization of auditory fields (30). This positioned the region of overlapping activations as within the caudal belt (caudo-medial and caudo-lateral fields), but also extending into primary field A1 and the caudal parabelt (including region Tpt), a location that is consistent with a vocalizationsensitive region reported in a previous study (16).…”
Section: Resultsmentioning
confidence: 99%
“…We defined as "active" any link from a cell x such that the output O(x,t) of cell x at time t is larger than θ pre , where θ pre ∈]0,1] is an arbitrary threshold representing the minimum level of presynaptic activity required for LTP (or LTD) to occur. Thus, given any two cells x and y linked with weight w t (x,y), the new weight w t+1 (x,y) is calculated as follows: (Romanski et al, 1999;Petkov et al, 2006) indicates that the auditory system consists of three main areas, A1, AB and PB; although these systems have been studied mainly in macaques, homologous areas of the human auditory cortex (Brodmann Areas 41, 42 and 22) lend themselves to an analogous parcellation (Uppenkamp et al, 2006). …”
Section: Appendix Amentioning
confidence: 99%